Electrochemical synthesis of Sn–Ag alloy coatings in sulphate solution - Vrublevskaya, Olga N.; Shikun, Marina A. (Journal of the Belarusian State University. Chemistry, 2019)
The optimal conditions for the electrochemical synthesis in the sulfate electrolyte of low-melting Sn–Ag alloy coatings used in the assembly of electronic equipment containing 7.1–8.3 at. % of silver and with total current yield of metals equal to 88.8–87.0 % are determined. It is established that electrochemical reduction of Sn(II) and Ag(I) on the surface of the alloy is accompanied by the process of contact displacement of Ag(I) with tin included into the coating. The process of contact displacement is intensified with the electrolyte temperature growth and leads to the increase in silver content in the alloy, to the appearance of dendrites on the surface of the coating due to its passivation.
Keywords: electrochemical deposition; alloy; silver; tin; eutectic; sulphate electrolyte; microstructure; electrolyte temperature